Utilisation of Agricultural Research and Extension Services by Rainfed Farmers - G.R. Desai; P.L. Manohari; T.D.S. Kumar (Journal of Agricultural Extension Management, 2025)
Agricultural research and extension are the two main interventions introduced in the country for transforming the agricultural sector over the last six decades. A massive infrastructure of research and extension, with central Institutions, Agricultural universities, KVKs and the departments of agriculture, has been created across the country to develop and transfer the technologies suitable to the farming communities. However the crucial aspect is the extent of utilization of these technologies and services by the farming community. This is especially important considering the fact that a majority of the farmers operate rainfed farming systems in critical, diversified, risk prone zones. Keeping these aspects in view the present study was undertaken with the following objectives